Diplomatic Relations with the Baburian Empire During the Reign of Bukhara Khan Abdulazizkhan (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This study examines the diplomatic interactions between Abdulaziz Khan, the designated figure of the Ashtarkhanid lineage, who assumed leadership subsequent to Nadr Muhammad Khan in the Bukhara Khanate, and Aurangzeb, the sovereign of the Baburi realm, utilizing primary sources and scholarly works.